Polymer-Supported Stereoselective Synthesis of Benzoxazino[4,3-b][1,2,5]thiadiazepinone 6,6-dioxides - Králová, Petra; Maloň, Michal; Volná, Tereza; Ručilová, Veronika; Soural, Miroslav (ACS combinatorial science, 2017)
Herein, we report the stereoselective synthesis of trisubstituted benzoxazino[4,3-b][1,2,5]thiadiazepinone 6,6-dioxides from polymer-supported Fmoc-Ser(tBu)-OH and Fmoc-Thr(tBu)-OH. After the solid-phase synthesis of N-alkylated-N-sulfonylated intermediates using various 2-nitrobenzenesulfonyl chlorides and bromoketones, the target compounds were obtained via trifluoroacetic acid (TFA)-mediated cleavage from the resin, followed by cyclization of the diazepinone scaffold. Except for the threonine-based intermediates, the inclusion of triethylsilane (TES) in the cleavage cocktail yielded a specific configuration of the newly formed C3 chiral center. The final cyclization resulted in minor or no inversion of the C12a stereocenter configuration.
Keywords: alkylace; cysteine; serine; Stereoisomerism; Alkylation; stereoselective synthesis; threonine; thiadiazoly; thiomorpholine; Cyclization; solid-phase synthesis; Cyclic S-Oxides; knihovny malých molekul; Small Molecule Libraries; Polymers; cyklické S-oxidy; Solid-Phase Synthesis Techniques; stereoizomerie; vztahy mezi strukturou a aktivitou; techniky syntézy na pevné fázi; cyklizace; bromoketone; triethylsilane; benzoxazinothiadiazepinone; Thiadiazoles; morpholine; polymery; Structure-Activity Relationship; nitrobenzenesulfonyl chloride